Analisis SWOT dan QSPM untuk Perumusan Strategi Pemasaran pada PT. Gerongan Surajaya - Nuraini Rahmawati; Anita Asnawi; Liling Listyawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
PT Gerongan Surajaya is a company that produces springbed mattresses and complementary items such as divans, pillows, and vacuum mattresses that have been established since 1992. In running its business, the right marketing strategy is needed in order to compete with similar or other competitors. The purpose of this research is to analyze the internal and external factors that influence and can influence marketing strategy-making decisions at PT Gerongan Surajaya. The research method was carried out in a descriptive qualitative way, and data collection was carried out by means of interviews, observations, and also literature reviews. The approach taken in this research is SWOT analysis (Strength, Weakness, Opportunity, Threats), IFE-EFE and IE matrix, SWOT matrix, and QSPM matrix. The results obtained from this study are known that the company's position is in the Grow and Build position with IFE results of 3,069 and EFE results of 3,241. Then in the QSPM matrix it is known that the priority development strategy that needs to be done is to always update and pursue the trends needed by the market based on the results of the first rank score, namely TAS, which is 0.76.